2011
DOI: 10.1039/c1dt10322a
|View full text |Cite
|
Sign up to set email alerts
|

Library of second-generation cycloruthenated compounds and evaluation of their biological properties as potential anticancer drugs: Passing the nanomolar barrier

Abstract: A library of 32 organoruthenium compounds has been synthesised. Known and novel C-N cyclometalated compounds as well as N-C-N and N-N-C pincer derivatives of this metal have been used in this purpose. Most of the compounds have been tested for their in vitro antitumoral behaviours, good to excellent activities have thus been found. Several of the newly synthesized compounds pass the symbolic barrier of the nanomolar range for their IC(50) indicating a critical improvement. The level of activity is tentatively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
72
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(78 citation statements)
references
References 52 publications
3
72
0
Order By: Relevance
“…Such values are in the same range as those obtained for 1·PF 6 . [16,29] In addition, as indicated above, 1·PF 6 also induces the ER stress pathway in a manner similar to that of several ruthenium complexes.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Such values are in the same range as those obtained for 1·PF 6 . [16,29] In addition, as indicated above, 1·PF 6 also induces the ER stress pathway in a manner similar to that of several ruthenium complexes.…”
Section: Resultsmentioning
confidence: 95%
“…[28] Ruthenium and osmium complexes with one terpyridine ligand and one monoanionic NCN pincer ligand have been prepared and studied against several cancer cell lines, and they showed good cytotoxic activities with IC 50 < 3 μM. [16,29] Therefore, tridentate ligands derived from polypyridines seem to be a good option for the stabilization of metalated iron compounds with potential cytotoxic properties. Additionally, the thriving interest in such iron pincer compounds is reflected in the fact that their structures have recently been modeled and various computational studies have been performed.…”
Section: Introductionmentioning
confidence: 99%
“…11-16) Pfeffer and colleagues 17,18) and Chao and colleagues 19,20) have found that some cyclometalated ruthenium(II) complexes are good candidates for becoming anticancer drugs. A cyclometalated ruthenium fragment with a metal-carbon σ bond is a crucial element for a potential anticancer drug.…”
Section: )mentioning
confidence: 99%
“…[5][6][7][8][9][10] Several ruthenium complexes that display an activity comparable to that of cisplatin have been described, and in some cases activities are even better. [11][12][13][14][15][16] Pfeffer and colleagues 17,18) and Chao and colleagues 19,20) have found that some cyclometalated ruthenium(II) complexes are good candidates for becoming anticancer drugs. A cyclometalated ruthenium fragment with a metal-carbon σ bond is a crucial element for a potential anticancer drug.…”
mentioning
confidence: 99%
See 1 more Smart Citation